Modelling of Maxwell’s equations using uniform finite elements - Moiseenko, V.E. (Вопросы атомной науки и техники, 2003)
The theory of numerical stability of weighted residuals schemes for Maxwell’s equations written in terms of electric field is presented. Basing on it, the numerically stable scheme using physical components of electric field and uniform trial functions is developed. The proposed scheme is tested in cylindrical geometry and compared with the numerically stable Galerkin scheme. The tests show the evidence of numerical stability of the scheme proposed. The convergence is monotonic and corresponds to the order of approximation. It is demonstrated that, unlike the Galerkin scheme, the scheme proposed is much less sensitive to the stiffness of the Maxwell’s equations in plasma. В роботі подана теорія числової стійкості схем зважених нев’язок, що застосовані до рівнянь Максвела з виключеним магнітним полем. На її основі розроблена чисельно стійка схема, яка використовує фізичні компоненти електричного поля та однорідні пробні функції. Для цієї схеми проведено тестування у порівнянні зі схемою Гальоркіна. Воно підтвердило числову стійкість запропонованої схеми. Аналіз збігання показав, що воно є монотонне і відповідне до порядку апроксимації. Тестові розрахунки продемонстрували, що в порівнянні зі схемою Гальоркіна запропонована схема є суттєво менш чуйною до жорсткості рівнянь Максвела в плазмовому середовищі. В работе представлена теория численной устойчивости схем взвешенных невязок применительно к уравнениям Максвелла с исключенным магнитным полем. На ее основе разработана численно устойчивая схема, использующая физические компоненты электрического поля и однородные пробные функции. Для этой схемы проведено тестирование в сравнении со схемой Галеркина. Оно подтвердило численную устойчивость предложенной схемы. Анализ сходимости показал, что она является монотонной и соответствует порядку аппроксимации. Тестовые расчеты продемонстрировали, что по сравнению со схемой Галеркина предложенная схема значительно менее чувствительна к жесткости уравнений Максвелла в плазменной среде.